A Study of Assessment of Partial Edentulous Patients Based on Kennedy’s Classification at Dhulikhel Hospital Kathmandu University Hospital - Sapkota, B; Adhikari, B; Upadhaya, C (Kathmandu University Medical Journal, 2015)
Background Oral health contributes significantly towards quality of life (QOL). Edentulousness falls in a special category among the various conditions of dental origin. Dietary intake and nutritional status is affected by poor oral health and loss of teeth. This will ultimately compromise general health. Objective To identify the frequency of Kennedy’s classification among partial edentulous patients and to compare occurrence among gender and between upper and lower arches and also to compare edentulousness among employed and unemployed population. Methods This study was carried out at Dhulikhel Hospital Dental Department. The study was conducted randomly among 194 patients in dental OPD who were partially edentulous. A structured pro forma was used to find out the edentulousness based on Kennedy,s classification. Results Among the Kennedy’s classification Class III was found to be most common. Among them females and unemployed group were found to have more edentulousness and upper arch was more common. It was also found that females were more conscious and get the replacement of missing teeth among which those having Class IV missing were replaced most often. Conclusion The Kennedy Class III partial edentulousness type is most commonly found in this study. Kathmandu Univ Med J 2013; 11(4): 325-327